How Rational and Competitive Is the Market for Mutual Funds? - Leippold, Markus; Rueegg, Roger (Review of Finance, 2020)
Abstract To explore the rationality and competitiveness of the mutual fund industry, we analyze the alpha of active and index mutual funds from a global sample of more than 60,000 equity and fixed income funds and test the null hypothesis that alphas to investors are zero. We distinguish between institutional and retail investors since there are significant differences in management fees, economies of scale, and information asymmetries between these two groups. Using a new robust statistical test, we cannot reject our null hypothesis for the majority of investment categories. We find that the average active fund has less exposure to traditional risk factors, but higher sensitivity to alternative risk premia. Fund persistence and the impact of size and fees add further support to our conclusion that the mutual fund industry is highly competitive, except for US domestic funds. This set of funds is excessively overfunded compared with other fund categories.